The effect of audit tool and linked achieved system (ATLAS) on auditor performance - Bertha Elvy Napitupulu; Indah Nurhayati; Francisca Hermawan; Kuncu Saragih; Oktavia Marpaung (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
Technological developments require all sectors to implement the use of information technology, including audit processes that transform manual audits into computer-based audit techniques. Computer-based audit techniques make it easier for auditors to collect evidence and evaluate data, thereby supporting the identification of material errors. The optimal use of computer-based audit techniques has a significant impact on the effectiveness of audit implementation. Public accounting firms have begun to use computerized audit techniques to improve the efficiency and effectiveness of the audit process. ATLAS (Audit Tool and Linked Achieved System) is one of the computer-based audit software that has become widely used in public accounting firms. ATLAS is audit software designed to improve the effectiveness and efficiency of audits through structured documentation, tracking of audit findings, and integration of historical data. The use of ATLAS software should significantly improve auditor performance, particularly in terms of the efficiency and accuracy of the audit process. This study aims to determine the effect of ATLAS usage on the performance of auditors from public accounting firms in Jakarta. Auditor performance is measured in terms of efficiency, effectiveness, and accuracy. The sample for this study consisted of 80 auditors from public accounting firms in Jakarta who had worked for at least one year using ATLAS. Data analysis was performed using regression analysis and simple linear correlation, the results of which showed that ATLAS had an effect on auditor performance, namely efficiency, effectiveness, and accuracy.